P 42 Congenital myasthenia in adult patients – a diagnostic and therapeutic challenge. Issue 10 (October 2017) - Ritter, C.; Cirak, S.; Abicht, A.; Lehmann, H.C.; Brunn, A.; Fink, G.; Schroeter, M.; Wunderlich, G.
Abstract : Congenital myasthenic syndromes (CMS) are a heterogenic group of mainly recessive inherited loss-of-function mutations of different molecular structures of the motor endplate leading to a defective neuromuscular transmission. They typically present in early childhood with ocular, bulbar and fatigable proximal muscle weakness. Occasionally symptoms may occur first in late childhood or even early adolescence. Here we report two patients who were first diagnosed CMS in early adulthood. In the first patient dysphagia was present in early childhood seen as perinatal hypoxic brain injury despite normal cranial MRI and remarkable cognitive development. By the age of 10 years the patient began to suffer from a fatigable general and ocular muscle weakness as well as bilateral ptosis. Electromyography was myopathic in absence of a decrement after repetitive stimulation. Furthermore, creatin kinase was normal and myasthenia-specific auto-antibodies were absent. Considering a mitochondriopathy a muscle biopsy was performed showing pronounced atrophy of single muscle fibers. By the age of 26 the patient was evaluated again and the differential diagnosis CMS was considered. Genetic diagnostics revealed a homozygous mutation in the CHRNA1-gen. Symptomatic treatment with pyridostigmine led to a significant clinical improvement. In the second case a 25 yo patient reported a fatigable proximal muscle weakness, dysarthria and impaired ocular muscle function since the age of 10. Furthermore, a high palate and mild dysmorphic signs were suspicious. Electromyography showed myopathic potentials. Blood tests and a muscle biopsy were normal. Finally, genetic testing revealed mutation in the COLQ-gen. Initiation of 3, 4-diaminopyridine treatment led to clinical improvement whereas salbutamol showed no supporting effect. These two patients show that the diagnosis CMS may be challenging. Clinical and diagnostic results may mimic primary myopathy or dystrophic muscle disease as well as mitochondriopathy. Furthermore pathological myasthenia-specific auto-antibodies targeting the motor endplate are absent. Finally, it is import to take the differential diagnosis CMS into account. Because of different treatment strategies the underlying genetic changes should be identified.